Changing trends in keratoplasty in the West of Scotland: a 10-year review. Issue 3 (6th July 2011) - Ting, Darren S J; Sau, C Y; Srinivasan, S; Ramaesh, K; Mantry, S; Roberts, F
Abstract : Background/aims: To review the indications and types of keratoplasty performed in the West of Scotland between 2001 and 2010. Methods: A retrospective analysis of the histopathological diagnoses of all corneal buttons submitted to the regional Ocular Pathology Laboratory (Glasgow, UK) between January 2001 and December 2010 was performed. Results: Between 2001 and 2010, a total of 921 keratoplasties were performed in the West of Scotland. These included 646 (70.1%) penetrating keratoplasties and 275 (29.9%) lamellar keratoplasties (LK). Keratoconus (n=264, 28.7%) was the leading indication for keratoplasty, followed by graft failure (n=177, 19.2%), Fuch's endothelial dystrophy (n=124, 13.5%), keratitis (n=106, 11.5%), pseudophakic/aphakic bullous keratopathy (n=88, 9.6%), endothelial failure (n=67, 7.3%), non-Fuch's corneal dystrophies (n=21, 2.3%), trauma (n=19, 2.0%), autoimmune/inflammatory diseases (n=16, 1.7%) and others (n=39, 4.2%). A significant increase in the proportion of LK over penetrating keratoplasty was observed during this 10-year period: from 14.1% LK (2001–2005) to 40.4% LK (χ 2 =71.78, p value<0.001). Conclusion: Keratoconus was the leading indication for keratoplasty in the West of Scotland. Both anterior LK and endothelial keratoplasty seemed to show an emerging trend as the procedures of choice for dealing with anterior and posterior corneal pathologies, respectively.